A Novel Integrative Methodology for Research on Pot-honey Variations During Post-harvest - Patricia, Vit; Bajaree, Chuttong; Norhasnida, Zawawi; Maria, Diaz; Jane Van, der Meulen; Hajar F., Ahmad; Francisco A., Tomas-Barberan; Gina, Meccia; Khanchai, Danmek; J. Enrique, Moreno; David W., Roubik; Ortrud Monika, Barth; et al. (Universidade Estadual de Feira de Santana, 2022)
This novel review of analytical methods for pot-honey research was intended to provide concise references to a 35-day post-harvest experiments at 30 °C, in an integrated study. Diverse methods were selected from specialized literature, from the AOAC (Association of Official Analytical Chemists), and the International Honey Commission. Besides the geographical and seasonal origin, the pot-honey I.D. consists of entomological and botanical identifications, the latter performed by acetolyzed or natural melissopalynology. The methods of this integrative study included: 1. Physicochemical analysis (Aw, color, moisture, pH, free acidity, lactone acidity, total acidity, hydroxymethylfurfural (HMF), and sugars by highperformance liquid chromatography HPLC), 2. Targeted proton nuclear magnetic resonance 1H-NMR metabolomics (sugars, ethanol, HMF, aliphatic organic acids, amino acids, and botanical markers), 3. Biochemical composition (flavonoids, polyphenols), 4. Antioxidant activity (ABTS 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid-free radical scavenging assay, DPPH 2,2-diphenyl-1-picrylhydrazyl radical scavenging assay, ferric reduction assay FRAP), 5. Microbial counts (aerobic plate, yeast and mold, Bacillus, and lactic acid bacteria count), 6. Honey microbiome profiling via independent-culture method: high-throughput bacteria and fungi based on amplicon sequencing approaches, 7. Sensory evaluation (odor, aroma, taste, persistence), and 8. Honey authenticity and biosurfactant tests by an interphase emulsion. A further section was included to provide basic information on the results obtained using each method. This was needed to explain the interacting components derived from pot-honey processing within the stingless bee nest and post-harvest transformations.